Hormonal based treatment of ovarian anaplastic ependymoma with anastrozole - Justin Wayne Gorski; Jolyn Sharpe Taylor; Jing Zhang; Jinsong Liu; Amir Anthony Jazaeri (Elsevier, 2017)
Objective: Ovarian anaplastic ependymoma is a rare gynecologic malignancy that poses diagnostic and treatment challenges. Treatment of sub-optimally debulked disease usually portends poor prognosis. Molecular testing of tumor specimen can identify more specific targets for additional therapy such as estrogen and progesterone receptors (ER/PR). Case: A 29-year-old woman presented with incidental finding of large bilateral adnexal masses and elevated CA 125. Biopsy proved anaplastic ovarian ependymoma with high ER/PR expression. She underwent sub-optimal surgical debulking followed by adjuvant chemotherapy with bleomycin, etoposide and cisplatin (BEP) which resulted in a partial response. Due to extensive residual disease she has been maintained on anastrozole for over fifteen months without increased tumor burden. Targeted somatic mutation testing was negative for all high risk clinically useful variants. Conclusion: Aromatase inhibitors may be considered in patients with extra-axial anaplastic ependymoma and can produce prolonged stable disease.